Pengajian Usuluddin di Kolej Islam Antarabangsa Sultan Ismail Petra (KIAS): Analisis dari Sudut Silibus Pengajian - Yaakob, Muhammad Nasron; Hamat, Mohd Fauzi (Jurnal Usuluddin, 2003)
This article attempts to analyse the syllabus of theology studies at the Department of Theology of Sultan Ismail Petra International College (KIAS), Kelantan. Examining the syllabus and comparing it with the syllabus of the same level of other colleges shows some strengths and weaknesses that should be improved. Some suggestions are raised to improve the study to ensure that it can produce students of international standard.